2021
DOI: 10.3390/ijerph18116029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Future Projection of Extreme Climate Events in the Yellow River Basin and Yangtze River Basin in China Using Ensembled CMIP5 Models Data

Abstract: The Yellow River Basin (YLRB) and Yangtze River Basin (YZRB) are heavily populated, important grain-producing areas in China, and they are sensitive to climate change. In order to study the temporal and spatial distribution of extreme climate events in the two river basins, seven extreme temperature indices and seven extreme precipitation indices were projected for the periods of 2010–2039, 2040–2069, and 2070–2099 using data from 16 Coupled Model Intercomparison Project Phase 5 (CMIP5) models, and the delta c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…In addition, the precipitation variability will be smaller in high-elevation regions, while the fluctuations in temperature in high elevations is expected to be larger than fluctuations in low elevations [59]. As reported by Niu et al [42], warming extremes were projected to increase while cold events were projected to decrease on the eastern Tibetan Plateau. The above descriptions support a portion of results from this study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, the precipitation variability will be smaller in high-elevation regions, while the fluctuations in temperature in high elevations is expected to be larger than fluctuations in low elevations [59]. As reported by Niu et al [42], warming extremes were projected to increase while cold events were projected to decrease on the eastern Tibetan Plateau. The above descriptions support a portion of results from this study.…”
Section: Discussionmentioning
confidence: 85%
“…The maximum and minimum temperatures have increased significantly at rates of 0.19 • C and 0.37 • C per decade, respectively [41]. A recent study has reported that the magnitude of the changes in extreme climate events in the Yangtze River basin is projected to increase with the increasingly warming climate [42]. These variations have exerted a considerable influence on society and the ecosystem, making climate change one of the most urgent challenges facing the YRB [40].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that GCMs is able to simulate some climatic factors on a regional scale (Seneviratne and Hauser, 2020;Quenum et al, 2021;Li et al, 2022). Numerous studies have also shown that the simulation effect of the multimodel ensemble is better than that of a single model, and the simulation uncertainty is smaller (Kim et al, 2020;Almazroui et al, 2021;Niu et al, 2021). Therefore, in this study, we selected 8 models with complete data for the period 1976-2100 in CMIP6 to simulate and project runoff in the SAYR.…”
Section: Datamentioning
confidence: 99%
“…e annual average precipitation is about 551.6 mm. e Yellow River Delta is rich in biodiversity and natural resources and has been extensively studied by scholars [34,35].…”
Section: Study Areamentioning
confidence: 99%